What would it take to break the world record in the men's triple jump - Graham-Smith, P.; Brice, P. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to bring together 30 years of athlete support and applied research into the horizontal jumps and develop a strategy for an elite athlete to challenge the World Record which has stood for over 27 years. Data on an elite triple jumper who has jumped over 18m was collected in a Diamond League competition and in training. Approach speed, phase distances, technical analysis and anthropometrical data were utilised to develop an interactive 7 segment model from which a new World Record was reconstructed. This study demonstrates a process of how to utilise biomechanical data and implement it into a high-performance setting, providing the coach with clear, objective and meaningful data from which they can set criteria to assist in developing performance.